Tourist activities focusing on antarctic penguins - Bertellotti, Nestor Marcelo; D'amico, Veronica Laura; Cejuela, Evelina (Annals of Tourism Research)
Nowadays there is unequivocal evidence of the ongoing climate change and the anthropogenic global warming. For penguin species that live in Antarctica, this is having significant impacts since warming is causing a decline in the abundance of Antarctic krill, their major food supply. The increase in the tourist activity in Antarctica makes it necessary to apply strategies for adapting to the climate change. Based on a case of study of penguin-watching tourism, it is proposed recommendations of the tourism policy grounded in strategies that minimise the impact upon a dynamic resource, which should adjust to the fluctuating and rapid condition of the climate change. Fil: Bertellotti, Nestor Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Cejuela, Evelina. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina